2017
DOI: 10.1111/opo.12355
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of Goldmann III, V and spatially equated test stimuli in visual field testing: the importance of complete and partial spatial summation

Abstract: PurposeGoldmann size V (GV) test stimuli are less variable with a greater dynamic range and have been proposed for measuring contrast sensitivity instead of size III (GIII). Since GIII and GV operate within partial summation, we hypothesise that actual GV (aGV) thresholds could predict GIII (pGIII) thresholds, facilitating comparisons between actual GIII (aGIII) thresholds with pGIII thresholds derived from smaller GV variances. We test the suitability of GV for detecting visual field (VF) loss in patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(80 citation statements)
references
References 44 publications
6
73
1
Order By: Relevance
“…21,[44][45][46] The age difference between individual subjects and the cohorts may therefore increase the variability within the dataset and confound the comparison of structure-function relationship between the normal and glaucomatous cohort. Hence, to minimize the variability imposed by intra-and intercohort age differences, the GCL thickness and DLS of all normal and glaucomatous subjects were age-corrected to the average age of the glaucomatous cohort using previously established regression analysis models as conducted in previous studies, 11,21,[24][25][26]31,32,45,47 including the commonly used SITAstandard algorithm of the HFA. 48 Specifically, for the GCL thickness, measurements from each normal and glaucomatous subjects were clustered into eight statistically separable classes and adjusted to match the average age of the glaucomatous cohort using a previously published conversion for all but the foveal area.…”
Section: Age Correctionmentioning
confidence: 99%
See 2 more Smart Citations
“…21,[44][45][46] The age difference between individual subjects and the cohorts may therefore increase the variability within the dataset and confound the comparison of structure-function relationship between the normal and glaucomatous cohort. Hence, to minimize the variability imposed by intra-and intercohort age differences, the GCL thickness and DLS of all normal and glaucomatous subjects were age-corrected to the average age of the glaucomatous cohort using previously established regression analysis models as conducted in previous studies, 11,21,[24][25][26]31,32,45,47 including the commonly used SITAstandard algorithm of the HFA. 48 Specifically, for the GCL thickness, measurements from each normal and glaucomatous subjects were clustered into eight statistically separable classes and adjusted to match the average age of the glaucomatous cohort using a previously published conversion for all but the foveal area.…”
Section: Age Correctionmentioning
confidence: 99%
“…21 The difference imposed by age between these cohorts is within the test-retest variability range of the instruments, [44][45][46][47][48][49][50][51][52][53][54][55][56] and even before correction, there were notable overlaps between the prediction interval for the regression curves of the two cohorts (data not shown). Regardless, DLS and GCc for the normal and glaucomatous cohort were adjusted to a common age equivalent using a wellestablished age-correction method, frequently used in prior studies by different investigators 11,21,[24][25][26]31,32,45,47 and regularly utilized by clinical test algorithms for the Humphrey Field Analyzer; SITA. 48 A subanalysis was conducted to further confirm the validity of the age-correction technique, and good fidelity was demonstrated between the glaucomatous subgroup, and the normal age-corrected and age-matched cohorts ( Supplementary Fig.…”
Section: Limitations Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This study was conducted in the context of renewed research interest in revising perimetric stimuli. For circular stimuli as used in conventional perimetry, defects tend to be deeper with smaller stimuli . However, two studies (one from our lab) found that large flickered sinusoids can yield similar defect depths as the much smaller size III stimulus, with increased spread of the data in deeper defects .…”
Section: Discussionmentioning
confidence: 81%
“…More recent studies have shown that equating for spatiotemporal summation characteristics can allow detection of functional losses in earlier stages of glaucoma . Simple modifications of test stimuli at different visual field test locations can specifically maximise defect detection, while maintaining the widest dynamic range of testing . Defects found with such stimuli have been shown to be commensurate with underlying, detectable structural loss, thereby potentially improving the structure‐function relationship (Figures and and see Figure A in Kalloniatis and Khuu) .…”
Section: The Problem Of Structure‐function Discordancementioning
confidence: 99%